Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Gene Mutations and Risk for Pancreatic Adenocarcinoma - McWilliams, Robert R. (2010)
BACKGROUND: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene are common in white persons and are associated with pancreatic disease. The purpose of this case-control study was to determine whether CFTR mutations confer a higher risk of pancreatic cancer. METHODS: In a case-control study, we compared the rates of 39 common cystic fibrosis–associated CFTR mutations between 949 white patients with pancreatic adenocarcinoma and 13,340 white controls from a clinical laboratory database for prenatal testing for CFTR mutations. The main outcome measure was the CFTR mutation frequency in patients and controls. RESULTS: Overall, 50 (5.3%) of 949 patients with pancreatic cancer carried a common CFTR mutation versus 510 (3.8%) of 13,340 controls (odds ratio, 1.40; 95% confidence interval, 1.04–1.89; P=.027). Among patients who were younger when their disease was diagnosed (<60 years), the carrier frequency was higher than in controls (odds ratio, 1.82; 95% CI, 1.14–2.94; P=.011). In patient-only analyses, the presence of a mutation was associated with younger age (median 62 vs 67 years; P=.034). In subgroups, the difference was seen only among ever-smokers, (60 vs 65 years, p=.028). Subsequent sequencing analysis of the CFTR gene detected 8 (16%) compound heterozygotes among the 50 patients initially detected to have 1 mutation. CONCLUSIONS: Carrying a disease-associated mutation in CFTR is associated with a modest increase in risk for pancreatic cancer. Those affected appear to be diagnosed at a younger age, especially among smokers. Clinical evidence of antecedent pancreatitis was uncommon among both carriers and noncarriers of CFTR mutations.